Natural Language Processing and Computational Linguistics : a Practical Guide to Text Analysis with Python, Gensim, SpaCy, and Keras. - Srinivasa-Desikan, Bhargav (Packt Publishing Ltd, 2018)
Discover how you can perform your own modern text analysis, to make predictions, create inferences, and gain insights about the data around you today. Learn how to harness the powerful Python ecosystem and tools such as spaCy and Gensim to perform natural language processing, and computational linguistics algorithms.